Cardiovascular causes of tracheobronchial compression: a decade experience in a Paediatric Congenital Heart Centre - Yubbu, Putri; Abdul Latiff, Haifa; Musa, Husna; Devaraj, Navin Kumar; Mohammad Razif, Nurul Adha; Sivalingam, Sivakumar; Samion @ Mingan, Hasri (Cambridge University Press, 2021)
Background: Vascular compression of the airway often complicates CHD management. This study evaluated the use of CT in determining cardiovascular causes, clinical manifestations, and outcome of tracheobronchial compression among children with CHD. Methods: A retrospective review of clinical records of all patients with CT scan evidence of tracheobronchial compression from January 2007 to December 2017 at National Heart Institute. Cardiovascular causes of tracheobronchial compression were divided into three groups; group I: vascular ring/pulmonary artery sling, II: abnormally enlarged or malposition cardiovascular structure due to CHD, III: post-CHD surgery. Results: Vascular tracheobronchial compression was found in 81 out of 810 (10%) patients who underwent CT scan. Group I lesions were the leading causes of vascular tracheobronchial compression (55.5%), followed by group II (34.6%) and group III (9.9%). The median age of diagnosis in groups I, II, and III were 16.8 months, 3 months, and 15.6 months, respectively. Half of group I patients are manifested with stridor and one-third with recurrent chest infections. Persistent respiratory symptoms, lung atelectasis, or prolonged respiratory support requirement were clues in groups II and III. Higher morbidity and mortality in younger infants with severe obstructive airway symptoms, associated airway abnormalities, and underlying complex cyanotic CHD. Conclusions: Vascular ring/pulmonary artery sling and abnormally enlarged or malposition cardiovascular structure were the leading causes of cardiovascular airway compression. A high index of suspicion is needed for early detection due to its non-specific presentation. The outcome often depends on the severity of airway obstruction and complexity of cardiac lesions.